Efficacy and safety of lenvatinib and pembrolizumab in the treatment of endometrial cancer: data from routine clinical practice in Russia - A. A. Rumyantsev; A. E. Protasova; M. Yu. Sheremet; A. Yu. Goryainova; M. V. Volkonskiy; A. G. Kedrova; S. V. Kuzmicheva; O. N. Aymamedova; Kh. S. Musaeva; S. M. Soroka; O. V. Romanchuk; V. N. Orlova; et al. (Опухоли женской репродуктивной системы)
Aim. To assess the efficacy and safety of lenvatinib and pembrolizumab for the treatment of mismatch repair-proficient endometrial cancer (EC) in routine clinical practice in Russia.Materials and methods. This multicenter, retrospective, cohort study included patients with recurrent and metastatic EC from 37 cancer centers in Russia treated between May 2020 and April 2023. Patients with histologically verified EC without microsatellite instability who received ≥1 course of pembrolizumab/lenvatinib therapy were included in the study. The primary endpoint was progression-free survival; the clinical characteristics of the patients were additionally analyzed, the objective response rate and the toxicity profile of therapy were assessed.Results. The study included 100 patients. Median age was 65 (30–83) years. The most common histologic tumor subtype was endometrioid adenocarcinoma (68 %); serous adenocarcinoma was diagnosed in 22 % of cases, other types of tumor – 10 % of cases. All patients had pMMR/microsatellite-stable tumors. The median progression-free survival was 7.75 months (95 % confidence interval 0.7–33.8), and a partial response to therapy was observed in 24 % of patients. Almost half of the patients (44 %) required dose reduction due to adverse events. The most common adverse events included fatigue (n = 26; 26 %), hypertension (n = 20; 20 %), and hypothyroidism (n = 14; 14 %).Conclusion. This study confirms the clinical efficacy of lenvatinib and pembrolizumab in patients with recurrent and metastatic EC without mismatch repair system deficiency (pMMR-tumors) in routine clinical practice.